Dermoscopy in the Diagnosis of Mycosis Fungoides: Can it Help? - Sarah Soliman; Wafaa Mohammad Ramadan; Amal Ahmed Elashmawy; Sameh Sarsik; Aimilios Lallas (Mattioli1885, 2023)
Introduction: The diagnosis of mycosis fungoides (MF) is challenging since it can mimic a variety of benign skin conditions. Multiple biopsies for histopathologic and immunohistochemical examination are required to diagnose MF. Dermoscopy is an affordable, non-invasive device with expanding indi-cations in dermatology, Objectives: To investigate the dermoscopic morphology of MF variants and assess the correlation between dermoscopic criteria, histopathologic, and immunohistochemical findings, Methods: We included 88 patients with several MF variants (classic, hypopigmented, hyperpigment-ed, poikilodermatous, erythrodermic, and folliculotropic).The diagnosis was histopathologically and immunohistochemically confirmed. Dermoscopic findings were collected, statistically analyzed, and correlated with the results of histopathology and immunohistochemistry, Results: All patients had MF diagnosis in H&E-stained sections.The majority revealed positive stain-ing with CD3, 4, 8 and negative CD7. Orange-red areas of discoloration, short linear, and spermato-zoa like blood vessels are the most frequent dermoscopic findings, while an analysis per MF variant was also performed.The frequently observed dermoscopic structures in classic MF were patchy whit-ish scales, dotted, short linear vessels, and spermatozoa-like vessels, Conclusions: Dermoscopy reveals a repetitive dermoscopic pattern in MF (non-homogenous pink to erythematous background, patchy areas of orange discoloration, patchy whitish scales, dotted and short linear blood vessels with some variations according to the clinical variant.